Analisis Pengaruh Kemasan Plastik Terhadap Lama Penyimpanan Sayuran Segar Pasca Ozonisasi: Studi Parameter Fisik, Water Vapour Transmission Rate (WVTR), dan Water Vapour Permeability (WVP) - Mualimin, Lulus; Sekar Arum, Mentari; Satika Dewi, Putri; Fahmi Briliansyah, Degita; Ihsan Alfarizi, Muhammad (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
Fresh vegetable commodities contribute significantly to food security and the national economy, but these products are easily damaged. Ozonation treatment and vacuum packaging are carried out to maintain product quality, reduce post-harvest losses, ensure food safety and extend the shelf life of vegetables. Choosing the right type of packaging is a challenge. The purpose of this study was to determine the effect of plastic packaging type on the storage time of fresh vegetables after ozonation based on physical parameters, water vapour transmission rate (WVTR), and water vapour permeability (WVP). The method used in this research is Randomized Group Design (RAK) with 3 treatments and 3 replicates and physical analysis using the scoring test method. The results of this study show that HDPE vacuum packaging has a better ability to withstand water vapor transmission rate (WVTR) and water vapor permeability (WVP) in all types of vegetables, as well as in physical testing including color, texture and appearance carried out based on scoring tests with an average value of 3, HDPE packaging has the best stability in preventing product quality deterioration to extend shelf life when compared to PP and LDPE packaging. These results are expected to be a recommendation for the type of packaging that is suitable in packaging fresh vegetable products to maintain product stability.